2016
DOI: 10.4103/1658-354x.179113
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of endotracheal tube cuff pressure: Instrumental versus conventional method

Abstract: Objective:To evaluate the conventional practice of endotracheal tube (ETT) cuff inflation and pressure measurement as compared to the instrumental method.Study Design:Prospective observational study.Place and Duration of Study:Department of Anaesthesia, King Saud University Hospital, Riyadh, Saudi Arabia (June 2014–July 2014).Methods:A total of 100 adult patients were observed according to the syringe size used Group-1 (10 ml) and Group-2 (20 ml) for ETT cuff inflation in general anesthesia. Patients with anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
1
21
1
8
Order By: Relevance
“…[6] Many authors recommended routine instrumental monitoring. [3,5,7] In our study also the proportion of subjects achieving normal pressure with clinical method is very low, as in 9 out of 10 persons the cuff pressure was higher than recommended value.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…[6] Many authors recommended routine instrumental monitoring. [3,5,7] In our study also the proportion of subjects achieving normal pressure with clinical method is very low, as in 9 out of 10 persons the cuff pressure was higher than recommended value.…”
Section: Discussionmentioning
confidence: 43%
“…Based on the available literature, it was observed that in 31% of the cases, a normal ETT cuff pressure was achieved. [3] At 95% level of significance and 10% absolute precision, the sample size was calculated as 82.13. Accounting 10% for non-response, the sample size was arrived at 90.3 and was finally rounded off to 100.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Despite the use of high-volume, low-pressure cuffs, certain patients remain at risk for cuff-induced laryngotracheal morbidity, even with short-duration anaesthesia. This has produced a growing interest in monitoring endotracheal tube cuff pressure intraoperatively and studying laryngotracheal morbidity as related to endotracheal cuff overinflation.…”
Section: Discussionmentioning
confidence: 99%